AIMING MILLENIAL AND ZILLENIAL GENERATIONS THROUGH THE REBRANDING OF NATIONAL POPULATION AND FAMILY PLANNING BOARD - Rizky Fauzia (Jurnal Ilmiah Wahana Bhakti Praja, 2021)
This study aims to describe the rebranding process of the National Population and Family Planning Board (BKKBN) using descriptive qualitative research methods. The data collection technique was carried out by means of document study and field observation. The results showed that the BKKBN rebranding had already started in 2009 after the reformation period or after the implementation of Regional Autonomy in Indonesia. However, in 2019 BKKBN initiated a rebranding formality in institutional regulations. This research describes in detail the implementation of BKKBN rebranding by carrying out four elements of rebranding, namely repositioning, renaming, redesigning, and relaunching. The results showed that the repositioning of the BKKBN was carried out by determining the target segmentation of the BKKBN audience that focused on the millennial and zillenial generations and changing the position of the BKKBN from fertility issues to "Sahabat Keluarga". In the process of renaming, BKKBN did not change its name because based on UU No. 52 Tahun 2009 is still relevant so that it only changes the vision and mission of the BKKBN to be more in line with current conditions. At the redesign stage, BKKBN involved the public by holding logo, tagline and jingle competitions, expert meetings and pre-testing the results of the competition. The new BKKBN logo is in the shape of a heart, butterfly and the colour is blue, the BKKBN tagline is "Berencana itu Keren". The relaunch process encountered many obstacles from resignation due to the maturation of the logo concept, tagline, and theme song as well as the Covid-19 pandemic. The soft launching of the winner of jingle competition and the rearrangement of Mars KB was held on December 19, 2019. The relaunch of the new BKKBN logo was carried out internally at BKKBN, all social media @BKKBNOfficial and dissemination of press release. The grand launching was held in conjunction with the XXVI National Family Day on June 29, 2020. Keywords: rebranding, communication, BKKBN, brand image